The Role of Users’ Socio-spatial Behaviour in Fostering Sustainable Retail District Projects in Bahrain - Afaf Ebrahim Mohamed; Najla Allani (Journal of Contemporary Urban Affairs, 2024)
This study examines users’ socio-spatial behaviour in promoting sustainable retail district projects in Bahrain. It evaluates how customer behaviour and movement impact the social sustainability of contemporary open-space shopping districts. By employing qualitative methods such as questionnaires, on-site observations, and expert interviews, this study investigates factors influencing consumer preferences and attractions to shopping districts. Findings reveal that the vitality of shopping districts is closely linked to meeting users’ needs, which fosters social sustainability. The study identifies key elements for a framework that can integrate social sustainability measures into shopping district designs. This framework aims to support stakeholders and designers in planning sustainable commercial projects in Bahrain, ensuring long-term success and vitality. Research highlights the importance of considering socio-spatial interactions in retail environments to enhance livability and user experience. By understanding these dynamics, designers can create retail districts that not only attract consumers but also contribute to the well-being and sustainability of the community. Insights gained from this study can guide the development of future retail projects, emphasizing the significance of socio-spatial behaviour in achieving sustainable urban design and planning.